The Handbook of development communicaton and social change (Malaysia: Wiley-Blackwell, 2014)
This book offers a valuable resource for advocates. scholars and communities engaged in long term and comprehensive struggles for social justice.
Part 1. Communicating Development and Social Change -- Part 2. Developing Strategic Communication for Social Change -- Part 3. Activist Approaches for Development and Social Change .
Includes bibliographical references and index.
Keywords: HANDBOOK; SOCIALIZATION; COMMUNICATION DEVELOPMENT